Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT Cahaya Mas Cemerlang - Dermawan, Fuzia Anissa; Jakfar, Jakfar (Peneliti.net, 2024)
The aim of this investigation is to explore the influence of organizational culture and work environment on the job satisfaction of employees at PT Cahaya Mas Cemerlang. All individuals participating in the research were affiliated with PT Cahaya Mas Cemerlang. To gather data, diverse quantitative methods including surveys, interviews, and observations were implemented. Employing the Slovin formula, a total of 65 respondents were selected for the study. The research methodology involved the utilization of SPSS 25 software, with a focus on employing a multiple linear regression analysis model. In the realm of this investigation, we've established a distinctive significance threshold (alpha) of 5%. Following the outlined methodology, the outcomes unearthed at PT Cahaya Mas Cemerlang unveil a noteworthy impact of organizational culture and work environment variables on employee job satisfaction, whether considered individually or concurrently. The statistical revelation indicates that a whopping 75% of the variations in employee job satisfaction can be attributed to these variables.